Webinar series 1/2021: strategies for winning industry grants - UiTM, Faculty of Applied Sciences (Faculty of Applied Sciences, 2021)
The first 2021 webinar series on strategies for winning industry grants organised by Deputy Vice-chancellor's Office (Researchand Innovation) UiTM.